POTENSI EKSTRAK KULIT JERUK KUNCI (Citrus microcarpa Bunge) SEBAGAI BIOREDUKTOR DALAM SINTESIS NANOPARTIKEL PERAK - Nadia Nia Nurulita; Athiah Masykuroh (Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University, 2022)
Nowadays silver nanoparticles (AgNPs) synthesized so often by plant extracts as a reductor. The synthesis of AgNPs was carried out by Citrus microcarpa Bunge fruit peel extract a reductor in various extract concentrations (10, 15, and 20%), concentration of AgNO3 solution of 0.15M and temperature of 700C. The presence of AgNPs was determined by color test and the formation of Surface Plasmon Resonance (SPR) using UV-Vis Spectrophotometer while to determine the morphology and size of the nanoparticles using Scanning Electron Microscope (SEM). The results of the analysis showed that AgNPs was formed at colloidal phase with dark brown color with wavelengths of 457.30 nm, 478.90 nm, and 422.80 nm for variation concentration of 10, 15 and 20% with slightly spherical, slightly elongated and jagged morphology with average size of 253.8 nm (10%), 254.2 nm (15%) and 253.9 nm (20%).